A comprehensive report on convective flow of fractional (ABC) and (CF) MHD viscous fluid subject to generalized boundary conditions - Imran, M.A.; Aleem, Maryam; Riaz, M.B.; Ali, Rizwan; Khan, Ilyas (Chaos, solitons and fractals, 2019)
•Boundary layer flow of viscous fluid is developed with the help Caputo–Fabrizio (CF) and (ABC) fractional derivatives.•Solutions for temperature, concentration and velocity fields are obtained by Laplace transform method.•As a result, we have observed that both the fractional models (CF) and (AB) are better in describing the memory effect of the physical problem.•(ABC) model is comparatively good in telling the history of the temperature, concentration and velocity fields. We have analyzed the magnetohydrodynaimcs (MHD) unsteady free convection flow of incompressible Newtonian fluid passing over an inclined plate through porous medium with variable temperature and concentration at the boundary. Additionally, we have also seen the effects of heat sink and chemical reaction. We have solved dimensionless equations governing the physical problem by Laplace transform method. Firstly, we have found the analytical results for concentration, temperature and velocity fields of classical model. After that we have extended the classical model to some fractional models specifically Caputo–Fabrizio (CF) and Atangana–Baleanu (ABC). Semi analytical results are attained for concentration, temperature and velocity fields for both models and then compared with solutions of classical one. Influence of Fembedded parameters on concentration, temperature and velocity domains can be perceived through MathCad software. As a result, we have observed that both the fractional models (CF) and (ABC) are better in describing the history of the physical problem. Further it is noted that, (ABC) model is well-suited in stimulating the history functions of temperature, concentration and velocity fields.